Aplicación del análisis por componentes principales en la evaluación de tres variedades de pasto (2012)
Objective: demonstrate how to use the principal-component analysis to reduce dimensionality in assessing three varieties of Ryegrass (Lolium sp. L.), namely, tetraploid hybrid (Foster), annual diploid (Southern Star), and annual tetraploid (Beefbuilder). Both the statistical properties and programming using the SAS statistical package are also highlighted. Results: The variables that defined the main factor for the three grass varieties were: height from the floor, middle width of the fully elongated last leaf, and biomass.